Significant role of internet of things (IoT) for designing smart home automation and privacy issues - Talal Alsharari, Dr.; Shayem Saleh Alresheedi, Dr.; Abdulaziz Fatani, Dr.; Ismail Yaqub Maolood, Dr. (International Journal of Engineering and Technology, 2020)
In this research paper the researcher emphasized the significant role of internet of things (IoT) for designing smart home automation with high security. The IoT is based on the internet and automated devices which are controlled by remotely using a PC, Smart phone, Tablet or other devices. The IoT is an intelligently connected devices and system which comprised of smart machines, environment, objects, and in-frastructure, Radio Frequency Identification (RFID), and sensors which will lead to meet the new challenges of Home Automation. In this research paper the researcher review the current research issues on Internet of Things(IoT) and Home Automation devices which are signif-icant to design the smart home or offices gadgets interact , seamlessly, surely control, monitor and improve accessibility from anywhere across the globe. The researcher used some of the statistical data from the STATISTA to show the current usage of smart home automation devices and it significant uses across the globe.Â Â